PERAN ORANG TUA DALAM PENGEMBANGAN KARAKTER DISIPLIN ANAK PADA PEMBELAJARAN DARING SISWA KELAS 2 SDIT INSAN KARIMA - Dewi Nabawi (Comm-Edu (Community Education Journal), 2021)
Parents play a very important role in the online learning process, because parents directly monitor children at home, so with parental assistance at home, it is hoped that children will easily adapt and form disciplined characters in online learning. The theories used in this study include the theory of the main role played by parents in developing children's character (Zubaedi, 2011), the role of parents in assisting children's learning (Lailiyatul & Faridhatul, 2020), the formation of disciplined characters (Tu'u, 2004) and online learning (Alimuddin, Tawany, & Nadjib, 2015). The data collection tools that the author uses in this study are: observation, interviews, literature study and documentation. This study uses a descriptive qualitative research with the subject of homeroom teachers, students and parents of grade 2 students at SDIT Insan Karima Nagrak Cangkuang. The results of this study include: the role of parents in developing the disciplined character of children in online learning is done by accompanying children during learning and trying to be a learning partner at home, being a motivator, facilitator so as to create a comfortable learning atmosphere, and giving rewards in the form of gifts that are useful for students. child. Constraints experienced by parents of SDIT Insan Karima students include lazy children in doing assignments, too busy with gadgets, bored, bored and easily distracted by other activities at home. The conclusion of this study is that parents of grade 2 SDIT Insan Karima students successfully carried out their role as parents in online learning companions well. This has an impact on student achievement and activity during online learning.